Leadership Development and Stress Management : Organizational Well-Being through Effective Leadership Practices - Hurem, Hana; Petrů, Jaroslav; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the role of leadership development in managing workplace stress and enhancing organizational well-being. While leadership is increasingly recognized as a key factor influencing employee stress and resilience, there remains a gap in understanding how development programs can be systematically designed to reduce emotional strain and promote healthier work cultures. This study addresses that gap by focusing on how structured leadership development programs, particularly those aimed at improving emotional intelligence, communication clarity, and adaptability, contribute to more supportive and effective organizational environments. Guided by an explanatory sequential mixed-methods design, the research begins with a quantitative survey of 200 employees across various sectors, examining the effects of toxic and supportive leadership behaviours, development program participation, and stress-related outcomes such as job satisfaction, engagement, and absenteeism intention. Statistical analysis was conducted using Jamovi software. The second phase involves 20 semi-structured interviews with leaders experienced in people management and formal leadership training. Using thematic analysis in Condens software, the qualitative phase offers contextual insight into how leadership behaviours are applied in practice and how leaders perceive their role in stress management. The findings confirm that emotionally intelligent, communicative, and adaptive leadership styles contribute significantly to employee well-being and performance, especially when supported by organizational consistency. Moreover, development programs were found to be most effective when integrated into daily routines and reinforced through feedback and coaching.
By combining empirical data and lived experience, this study contributes to academic research and offers practical strategies for embedding leadership development as a long-term approach to organizational well-being.
Vedoucí práce: Jaroslav Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses